2013
DOI: 10.1111/gwao.12010
|View full text |Cite
|
Sign up to set email alerts
|

Women Constructing Masculinity in Voluntary Firefighting

Abstract: Within gender studies, research and theorizing have used archetypal ‘masculine’ occupations to explore how masculinity is accomplished and practised in social interaction. In contrast, little work has explored how masculinity is constructed in the voluntary sector. In this paper, we address this gap by exploring how masculinity is constructed and experienced by women volunteers who are active firefighters in rural and regional Victoria. Firefighting is widely recognized as a non‐traditional occupation for wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Ainsworth et al (2014) note this in their study of current and former female CFA volunteers. Ainsworth et al (2014) note this in their study of current and former female CFA volunteers.…”
Section: The Cfa As a Male-dominated And Masculinized Organizationmentioning
confidence: 87%
See 1 more Smart Citation
“…Ainsworth et al (2014) note this in their study of current and former female CFA volunteers. Ainsworth et al (2014) note this in their study of current and former female CFA volunteers.…”
Section: The Cfa As a Male-dominated And Masculinized Organizationmentioning
confidence: 87%
“…In other localities, it has been suggested that the rural or wildland firefighter lacks the same cultural prestige as an urban counterpart but, in Australia, this does not appear to be the case. This can be seen through conformity to a particularly valorized kind of rural hegemonic masculinity (Tyler & Fairbrother, 2013a), often with links to the military (Ainsworth et al, 2014) and notions of militaristic-style heroism (Schauble, 2002). This can be seen through conformity to a particularly valorized kind of rural hegemonic masculinity (Tyler & Fairbrother, 2013a), often with links to the military (Ainsworth et al, 2014) and notions of militaristic-style heroism (Schauble, 2002).…”
Section: Fire Services In Rural Australiamentioning
confidence: 99%
“…A further differentiation is often made between formal and informal volunteering: formal volunteering is "unpaid labour undertaken in the public sphere" (Oppenheimer, 2001 , p. 2) often in association with volunteer organizations while informal volunteering is less structured unpaid work, that occurs outside the scope of volunteer organizations, often in the form of lending assistance to neighbours or extended family (Ainsworth, Batty, & Burchielli, 2013 ). Those who adopt narrower defi nitions of volunteering exclude informal helping given to family members, arguing that familial obligation negates the 'voluntary' nature of voluntary work (e.g.…”
Section: Characteristics and Motivations Of Older Volunteersmentioning
confidence: 99%
“…Through repeated performance, gendered identities are established and maintained and the balance of power between masculinities and femininities is negotiated. As noted above, within traditionally masculine workplaces, women often adopt masculine patterns of dress, speech and cultural practices as a means of claiming honorary masculinity (Ainsworth, Batty, & Burchielli, 2014;Dryburgh, 1999;Greed, 2000;Maupin & Lehman, 1994;Pilgeram, 2007;Powell et al, 2009;Wasserman & Frenkel, 2015). As noted above, within traditionally masculine workplaces, women often adopt masculine patterns of dress, speech and cultural practices as a means of claiming honorary masculinity (Ainsworth, Batty, & Burchielli, 2014;Dryburgh, 1999;Greed, 2000;Maupin & Lehman, 1994;Pilgeram, 2007;Powell et al, 2009;Wasserman & Frenkel, 2015).…”
Section: Introductionmentioning
confidence: 99%